Synthesis, biological evaluation and molecular modeling studies on novel quinonoid inhibitors of CDC25 phosphatases - Emilie Evain-Bana; Lucie Schiavo; Christophe Bour; Don Antoine Lanfranchi; Simone Berardozzi; Francesca Ghirga; Denyse Bagrel; Bruno Botta; Gilles Hanquet; Mattia Mori (Taylor & Francis Group, 2017)
The cell division cycle 25 phosphatases (CDC25A, B, and C; E.C. 3.1.3.48) are key regulator of the cell cycle in human cells. Their aberrant expression has been associated with the insurgence and development of various types of cancer, and with a poor clinical prognosis. Therefore, CDC25 phosphatases are a valuable target for the development of small molecule inhibitors of therapeutic relevance. Here, we used an integrated strategy mixing organic chemistry with biological investigation and molecular modeling to study novel quinonoid derivatives as CDC25 inhibitors. The most promising molecules proved to inhibit CDC25 isoforms at single digit micromolar concentration, becoming valuable tools in chemical biology investigations and profitable leads for further optimization.